Efficient (3S)-Acetoin and (2S,3S)-2,3-Butanediol Production from meso-2,3-Butanediol Using Whole-Cell Biocatalysis - Yuanzhi He; Feixue Chen; Meijing Sun; Huifang Gao; Zewang Guo; Hui Lin; Jiebo Chen; Wensong Jin; Yunlong Yang; Liaoyuan Zhang; Jun Yuan (Molecules, 2018)
(3S)-Acetoin and (2S,3S)-2,3-butanediol are important platform chemicals widely applied in the asymmetric synthesis of valuable chiral chemicals. However, their production by fermentative methods is difficult to perform. This study aimed to develop a whole-cell biocatalysis strategy for the production of (3S)-acetoin and (2S,3S)-2,3-butanediol from meso-2,3-butanediol. First, E. coli co-expressing (2R,3R)-2,3-butanediol dehydrogenase, NADH oxidase and Vitreoscilla hemoglobin was developed for (3S)-acetoin production from meso-2,3-butanediol. Maximum (3S)-acetoin concentration of 72.38 g/L with the stereoisomeric purity of 94.65% was achieved at 24 h under optimal conditions. Subsequently, we developed another biocatalyst co-expressing (2S,3S)-2,3-butanediol dehydrogenase and formate dehydrogenase for (2S,3S)-2,3-butanediol production from (3S)-acetoin. Synchronous catalysis together with two biocatalysts afforded 38.41 g/L of (2S,3S)-butanediol with stereoisomeric purity of 98.03% from 40 g/L meso-2,3-butanediol. These results exhibited the potential for (3S)-acetoin and (2S,3S)-butanediol production from meso-2,3-butanediol as a substrate via whole-cell biocatalysis.